2006
DOI: 10.2131/jts.31.219
|View full text |Cite
|
Sign up to set email alerts
|

A Reevaluation of the Threshold Exposure Level of Inhaled Jp-8 in Mice

Abstract: -C57BL/6 mice were nose-only exposed to JP-8 jet fuel at average concentrations of 45, 267, and 406 mg JP-8/m 3 for 1 hr/d for 7 days to further test the hypothesis that exposure to JP-8 concentrations below the current permissible exposure level (PEL) of 350 mg/m 3 will induce lung injury, and to validate a new "in-line, real-time" total hydrocarbon analysis system capable of measuring both JP-8 vapor and aerosol concentrations. Pulmonary function and respiratory permeability tests were performed 24 to 30 hr … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 20 publications
(19 reference statements)
0
20
0
1
Order By: Relevance
“…This method has been duplicated from the previous jet fuel exposure studies performed in our laboratory (Herrin et al, 2006). Both fuel (Syntroleum, Tulsa, OK, USA) vapor/aerosol mixture were generated using a Lovelace jet nebulizer (Model 01–100, IN-TOX, Albuquerque, New Mexico, USA).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…This method has been duplicated from the previous jet fuel exposure studies performed in our laboratory (Herrin et al, 2006). Both fuel (Syntroleum, Tulsa, OK, USA) vapor/aerosol mixture were generated using a Lovelace jet nebulizer (Model 01–100, IN-TOX, Albuquerque, New Mexico, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Animals were exposed over a period of seven consecutive days for one hour/day at 53 mg/m 3 (80 ppm THC, Figure 1) concentration for both JP-8 and S-8. The exposure protocol was chosen based on our recent study that initially indicated cellular alterations in terminal airways at this exposure level (Herrin et al, 2006). Control mice were exposed to ambient air for one hour/day each day for seven consecutive days.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…At 45 and 406 mg/m 3 , the vacuole volume density of lamellar bodies was increased, which is indicative of increased surfactant production. In addition, detachment of the epithelial cells of the airways was observed that was not dependent on the concentration (Herrin et al 2006).…”
Section: Studies With Aerosolmentioning
confidence: 92%